Resilience Building Among Adolescents From National Guard Families: Applying a Developmental Contextual Model. (May 2015) - Baptist, Joyce; Barros, Patricia; Cafferky, Bryan; Johannes, Elaine
A better understanding of resilience building in military-connected children is needed to serve the needs of military families and sustain the security of the United States. This study explored the development of resilience in 30 adolescents from National Guard families that had been deployed. Using thematic analysis, we found that military-connected adolescents are affected by events in settings far beyond their control—political and civil upheavals in foreign lands, military cultural values, societal perception of the military and of wars, and communities' responses to military families. When comfort was not offered by familiar social and school networks, these adolescents had only their families to which they could turn. The extent to which adolescents can depend on parents for comfort was influenced by the quality of the parental relationship. Even when parents were available, adolescents were inclined to uphold the military value of personal courage and withdraw to self-soothe.